2021
DOI: 10.1007/s10805-021-09392-7
|View full text |Cite
|
Sign up to set email alerts
|

Combating Academic Corruption and Enhancing Academic Integrity through International Accreditation Standards: The Model of Qatar University

Abstract: Academic institutions aim at achieving the highest standards of education and learning. Consequently, they prohibit academic corruption such as cheating or plagiarism. This article examines how international accreditation and quality assurance standards embody academic integrity as a main factor in deciding whether an academic institution should be accredited, and what ranking should an academic institution acquire in a competitive contest for educational excellence. Academic integrity is broadly defined to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…One of the essences of formal education is to bring uniformity in learning so that a common form of assessment can be used to get the required feedback on the set goals. It was, therefore, vital to ensure that respondents have the fundamental educational qualification that justifies their employment and consequently enhance their work (Mattar, 2022) assessed every year with a common law. The results in Table 1 indicate that the least educational qualification for the respondents was a Bachelor of Science (BSc) in procurement and/or supply chain management.…”
Section: Resultsmentioning
confidence: 99%
“…One of the essences of formal education is to bring uniformity in learning so that a common form of assessment can be used to get the required feedback on the set goals. It was, therefore, vital to ensure that respondents have the fundamental educational qualification that justifies their employment and consequently enhance their work (Mattar, 2022) assessed every year with a common law. The results in Table 1 indicate that the least educational qualification for the respondents was a Bachelor of Science (BSc) in procurement and/or supply chain management.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of guidance is only found in Islamic Boarding School education in the form of Tahfidzul Qur'an Education which can have a strong impact on character development (Mohamed, 2014;Wahyuni & Syahid, 2019). The coaching model in Islamic boarding schools consists of three integrated environments, namely the school environment, the dormitory environment, and the environment where the Islamic students play (Nakamura & Nishino, 1993;Mattar, 2021). In these three environments, students are always provided with coaching by dividing the time of Islamic students into three times, namely rest time, study time, and worship time.…”
Section: Figure 1 Corruption Crime Recapitulationmentioning
confidence: 99%
“…By classifying the research project into the cluster that already been identified in the MRDCS catalogue, the needs to match the research area of supervisor and student become more feasible. Furthermore, the risk of misrepresentation of qualification and credentials (Mattar, 2021) as academic malpractice which is one of the issue in academic integrity can be minimized during supervisor appointment. Thus, the next research question is:…”
Section: Research Experience Indicator: H-index Vs Research Projectmentioning
confidence: 99%